Uma compreensão daseinsanalitica da existência fibromiálgica por meio de imagens postadas em grupos de apoio no Facebook - Godoy, Sonia Maria (2017)
This research aimed to reach an daseinsanalytik understandment to the female experiences of fibromyalgic existence. The data for this comprehensive analysis were taken from images and narrations in support groups in Facebook. The biological sciences define fibromyalgia as a pathology that causes chronic and difuse musculoskeletal pain, it does not cause deformities and also don´t show any clinical evidence in images or fisiophatological exams. Phenomenology sees this matter through the slant of existence, for daseinsanalyse pathology is a way of the restricted being in your existencial possibilities of the accomplishment of the daily life. Fibromyalgia represents a public health issue with significant psychosocial and economical impacts, specially because it is hard to treat and the pain can cause severe incapacity, absenteeism, social and professional isolation, low self-worth feelings and emocional lability. The scope of this research is qualitative, in which were selected images and coments posted from 03/26/2016 to 04/10/2016 that showed any kind of register manifested through coments, sharings and/or emoticon reactions. The images and and reports were organized in groups of meaning. The categories given by Critelli (2006) for the unfolding of reality, guided the research and the data analysis: Unveiling, Revelation, Testemony, Accuracization and Authentication. The post reports confirm the dificulty in diagnosing, reveal a compromised quality o life with great restriction in the freedom to accomplish their existence crossed by chronic pain, associated with disturbing manifestations of fatigue, sleeping disorders, depression, among others. The affective shades most presente in the images are fear, despair, indignation, aphaty, discouragment and unhappines. This images and narratives give visibility to a existence that develops in a perennial and disturbing experience of pain, they narrate explicitly feelings of loneliness and existencial abandonment and reveal indignation with the lack of care, indiference and ignorance from people and health professionals that surrounds them. The fibromyalgic existence is way of beeing in the world that expresses a lot of suffering and that requires interdisciplinar care and research in different areas to bring enlightment and knowledge to fibromyalgic people as well as to professionals and people related to the patients that deal with this complexity